PENGUJIAN DAMPAK BANK-SPECIFIC DAN MACROECONOMIC TERHADAP PROFITABILITAS - Mutiara Auzi; Ruhadi Ruhadi; Marwansyah Marwansyah (I-Finance Journal, 2023)
This research aims to examine the impact of bank-specific and macroeconomic factors on profitability (ROA and ROE) in BPRS in Indonesia and the role of FDR as an intervening variable. This research uses analytical techniques Partial Least Square Structural Equation Model (PLS-SEM). The population was obtained from BPRS data recorded by OJK during 2017-2021. The total of sample are 154 BPRS through purposive sampling. The results showed that bank-specific factors through the DER variable did not affect profitability, BOPO negatively affected profitability, and NOM affected profitability. While macroeconomic factors through the GDP-Prov and Unemp variables do not affect profitability. Furthermore, the FDR affects ROA and does not affect ROE. then bank-specific factors through the DER variable have a positive FDR, BOPO negatively affect FDR, and NOM does not affects FDR. Meanwhile, macroeconomic factors through GDP-Prov did not affect FDR and Unemp negatively affected FDR. FDR does not mediate the affect of DER, BOPO, NOM, GDP-Prov and Unemp on profitability. The conclution is in Partially, not all variables affect profitability and there is no mediating role of the FDR variable between bank-specific and macroeconomic factors on profitability.